Environmental impact of a series of flash flood events on a hypersaline subtropical system in the Northwestern Arabian Gulf. (February 2022) - Ahmed, Ayaz; Al-Said, Turki; Madhusoodhanan, Rakhesh; Naqvi, S. Wajih A.; Sarkar, Amit; Fernandes, Loreta; Thuslim, Fathima; Al-Zakri, Waleed; Al-Yamani, Faiza
Abstract: A series of flash floods that swamped urban drainage systems in Kuwait in November–December 2018 drastically altered coastal hydrography. The phytoplankton responded quickly to the nutrient supply from land and reduced salinity despite elevated turbidity, as evident from rapid increases in chlorophyll a and net community production. Microphytoplankton was dominated by diatoms and the photosynthetic ciliate Myrionecta rubra . Both field observations and microcosm experiments suggested that although increased nutrient availability stimulates diatom growth, microzooplankton grazing controls their outbursts. This study revealed that in a hypersaline system similar to the northern Arabian Gulf, extreme events like flash floods have immediate but short-lived corollaries on coastal phytoplankton due to synergistic effects of bottom-up and top-down factors. The patterns are comparable to those reported from other tropical and sub-tropical systems. Highlights: Flash floods in November 2018 greatly impacted biogeochemistry of NW Arabian Gulf. Low salinity, high NH4 + restricted close to coast; nutrient entrainment from seafloor. Rapid response (growth) of phytoplankton (including diatoms) to nutrient enrichment Heterotrophs rapidly consumed photosynthesized organic matter; high respiration rates. Local response followed by regional signal arising from Shatt al-Arab River discharge